STUDI EKSPERIMENTAL PENGARUH PANJANG STRUKTUR HANGING BREAKWATER TERHADAP TRANSMISI GELOMBANG - Mulyawan, Deni; Paotonan, Chairul; Rahman, Sabaruddin (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2022)
Breakwaters are highly effective breakwater constructions that can be used to protect harbor waters by interrupting wave energy coming from the deep sea. Widely used breakwaters today are of the pile type, both natural and artificial. The drawback of rock breakwaters is that they are large in size and therefore very expensive to issue. Therefore, a new type of breakwater is needed that is smaller in size and cheaper to build. One solution that can be applied is a suspended breakwater. The purpose of this study is to determine the effect of wave parameters on the coefficient of wave transmission through a suspended breakwater. The research was conducted at the Marine Technology Research Laboratory, Hasanuddin University. The parameters in this study were carried out with 5 variations of wave height, 5 variations of wave period (T), and 3 variations of model length (L). From the results of the research we have done, it can be concluded that the value of the transmission coefficient (Kt) is inversely proportional to the steepness of the wave (Hi/L). Figure 3 shows that when compared between model variations (L1 = 40 cm; L2 = 50 cm; and L3 = 60 cm) with depth conditions (d = 70 cm) and with period variations (T 1; T 1.2; T 1.5; T 1.8 and T2 s), it can be seen that the Kt value is lower in the third model variation, L3 = 60 cm with a value of 0.095 < Kt < 0.53.